Environmental Performance and Press Freedom Within an Economical Framework - TURCENIUC, Alexia-Raluca (Studia Universitatis Babeș-Bolyai Negotia, 2024)
The purpose of this work is to investigate novel determinant factors of environmental performance such as press freedom and voice and accountability. Having reviewed the specialized literature in this field, one can observe and analyse the differentiated magnitude of the impact press freedom imprints on the Environmental Performance Index and the greenhouse gas emissions on the other, for a generous sample of countries, according to their development levels: high income, upper middle income, lower-middle income and low-income countries. The results support the positive effect of press freedom upon lowering greenhouse gas emissions and improving the overall environmental performance of nations, particularly for the subsample of low-income countries. The current findings are robust to several proxies and control variables. JEL classifications: Q56, O44, K32 Article History: Received: June 22, 2024; Reviewed: August 29, 2024; Accepted: September 17, 2024; Available online: September 23, 2024.